The Influence of Shaolin Teaching to Houjieâ€™s Personality Change in Shaolin Filmï¼ˆ2011) å°‘æž—æ•™ä¹‰å¯¹ä¾¯å‚‘åœ¨ã€Šæ–°å°‘æž—å¯ºã€‹ç”µå½±ä¸äººæ ¼å˜åŒ–çš„å½±å“ - Sufianto, Agustinus; Tantra, Jemmy; Gunadi, Fenny (Bina Nusantara University, 2015)
New Shaolin is a famous film from China. The story tells about Houjie?s life and his personality change. Shaolin?s positive influence in Houjie?s life is the main purpose of this research. Research used references and the theory of Sigmund Freud of ID, Ego and Superego to analyze Houjie?s personality change. Result shows thatafter receiving Shaolin?s teaching, he became a better man. In Shaolin, Houjie was forgiven. Shaolin?s teaching such as chanting a scripture can help improve his thoughts. Reflection and Kungfu brought Houjie out of his revenge and bad emotion, also bring harmony to his thoughts and heart. Houjie?s pre-character was dominated by his ID, but after he had entered Shaolin and learned Shaolin?s teaching, Houjie studied how to reach balance in 3 factors mentioned in the theory of personality.